How Effective are Government R&D Subsidies: The Empirical Evidence - Stefan Fölster (The Research Institute of Industrial Economics (IUI), 1987)
Government subsidized industrial R & D stands for a large and increasing segment of the total R & D conducted. Yet very little is known about the effectiveness of such subsidies. This paper summarizes the empirical literature concerning direct project subsidies, tax credits, and support for industrial research institutes. This helps to identify what makes government policy effective from the government's perspective and how it affects firms.
Keywords: H21; H23; O31; 330; Subsidies; R&D; summary; Industrieforschung; Forschungsfinanzierung; Theorie